Pulmonary function tests in granite quarry workers in Kuppam, Andhra Pradesh - M. K., Jayalakshmi; M., Margaret Mary; Priyadarshini, Caroline; Kumar, S. S. Vinay (International Journal of Research in Medical Sciences, 2025)
Background: Quarrying is the process by which rock, sand, gravel, or other minerals from the earth are removed to produce materials for construction work and other uses. During the process of quarrying, large amounts of dust particles of heavy metals, silica, and organic solvents are emitted from the earth’s surface. Kuppam region of Andhra Pradesh is famous for the green coloured granite stone which has global demand, which is specifically found in the Kuppam and surrounding villages, hence number of quarries are more and causing respiratory diseases of local quarry workers. Methods: The study was conducted in the department of physiology with total of 50 quarry workers for more than or equal to 5 years duration of working, both gender is randomly selected between 25-55 years of age. 50 Apparently normal healthy individuals of both genders were chosen from 5 km away from the quarry area as the control group. Ethical approval for the study protocol was obtained from institutional ethical clearance committee (IECC). After inclusion and exclusion criteria, lung function tests were done in quarry and the normal healthy subjects. Results: There was a statistically significant change in FEV1, FVC and PEFR among quarry workers. Conclusions: Not only quarry workers but also nearby residing population were also at the risk of deterioration of lung function tests.